2018
DOI: 10.1080/02670836.2018.1475919
|View full text |Cite
|
Sign up to set email alerts
|

Designing steel to resist hydrogen embrittlement: Part 1 – trapping capacity

Abstract: A novel steel has been designed for use in the oil and gas industry, displaying properties comparable with the currently available F22 grade and possessing the additional quality of excellent hydrogen trapping capacity. Its high strength is derived from a martensitic microstructure containing a dispersion of fine vanadium-molybdenum carbides that evolve during thermal treatments. If the tempering cycle is controlled such that the precipitates maintain a degree of coherency with the matrix, then they act as hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The value obtained is listed in Table 1; the sensitivity to N (c) T will be explored, as increasing the carbide content is the main strategy in designing materials with beneficial traps and intrinsic resilience [31,32].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The value obtained is listed in Table 1; the sensitivity to N (c) T will be explored, as increasing the carbide content is the main strategy in designing materials with beneficial traps and intrinsic resilience [31,32].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the critical value of C L at which embrittlement is observed must be within the plateau values of C Lmax,N predicted for f = 0.1 and f = 1 Hz. Results for the standard carbide trap density, N [31]. Increasing the trap density decreases the diffusion coefficient, see (5), and accordingly, the diffusion of lattice hydrogen within each cycle is reduced, leading to a lower value of C Lmax,N .…”
Section: Hydrogen-trap Interaction: Can It Be Used To Mitigate Fatigue?mentioning
confidence: 98%
See 2 more Smart Citations
“…Their findings imply that the hydrogen content can be decreased below the embrittlement threshold if D e is reduced, suggesting that materials can be engineered to bring down their hydrogen diffusivity and susceptibility to hydrogen-assisted fatigue crack growth. The effective diffusivity of materials can be reduced by increasing the density of beneficial traps -microstructural trapping sites that are not involved in the fracture process [27,28]. Fernández-Sousa et al [26] showed that increasing the density of carbides by 3 orders of magnitude in a CrMo steel enabled extending by an order of magnitude the regime of safe frequencies at which hydrogen has no effect.…”
Section: Introductionmentioning
confidence: 99%